A lesson from Juana Isang aral mula kay Juana - Bravo, Becky; Ranola, Jonathan; Pastor, Boots S. Agbayani (Quezon City Lampara Publishing House, Inc., 2011)
"The young girls on the island are taught how to weave and sew, while the young boys are taught how to fish. But Juana is confused by weaving cloth and sewing clothes. Instead, she asks her father to teach her how to fish-despite the protests, clucking of tongues, grunts of her townmates on the whole island."
Stories with moral values.
Text in English and Filipino.